Diversity of Annelids in the Kapuas and Melawi Rivers - Yakobus Bustami; Kurnia Kurnia; Markus Iyus Supiandi (Faculty of Science and Technology Universitas Islam Negeri Raden Fatah Palembang, 2019)
The presence of Annelida animals in water is one indicator of polluted water. The purpose of this research was to determine the diversity of Annelida phylum in the Kapuas and Melawi rivers. This research used an exploratory method to determine the diversity of annelids in the Kapuas and Melawi rivers. Sampling was carried out in 2 regions representing the left and right sides of the river, both upstream and downstream of the river. The findings of the research show that there are two classes of annelid phyla, namely the Oligochaeta and Hirudinae classes. Oligochaeta class is represented by Tubifex sp, Lumbricus terrestris, and Pharetima sp. species while Hirudinae class is represented by Haemodipsa sp. Species. The number of Annelids found in the Kapuas river for Tubifex sp. numbered 7 species, Lumbricus terrestris numbered 53 species and Pharetima sp. numbered 14 species. The number of Annelids found in the Melawi river for Tubifex sp. numbered 1 species, Lumbricus terrestris numbered 23 species, Pharetima sp. numbered 8 species and Haemodipsa sp amounted to 2 species. The presence of Tubifex sp. in the Kapuas and Melawi rivers shows that the quality of the river waters begins to be polluted.